Effect of dietary β-mannanase supplementation on growth performance, digestibility, and gene expression levels of Cyprinus carpio (Linnaeus) fingerlings fed a plant protein-rich diet - Dawood, Aneesa; Shi, Weibin (Frontiers in Veterinary Science, 2022)
The aim of this study was to assess possible beneficial effects of dietary β- mannanase supplementation on the nutrient digestibility, growth performance, digestive and metabolic enzymes activity and immune response of common carp (Cyprinus carpio) fed plant-protein rich diets. An experiment was conducted in triplicate and a total of 225 fingerlings of common carp with an average body weight of 13.17±0.12g were stocked in 15 fiberglass tanks (15 fish/tank). Five dietary treatments (control 35% crude protein, plant-rich basal diet without supplement and four diets supplemented with β-mannanase from two sources (commercially available and locally isolated), each at two dosage levels (500 and 1000U/kg diet) were prepared and fed to respective groups of fish, twice a day (8:00 AM & 4:00 PM) at 4 % body weight. During the trial, changes in the level of DO and temperature ranged from 5.5 to 6.1 mg L-1 and 21.5 to 23.5°C respectively. At the end of the feeding experiment, all fish in each tank were weighed and counted to determine growth parameters, while for the study of other indices, 9 samples/treatment group were selected. The results of the study indicated a positive effect of both sources and dosage levels of β-mannanase supplementation on all studied indices, i.e., significantly improved (P<0.05), growth performance (%weight gain, specific growth rate), survival %, hematological indices (RBC, Hb, HCT, MCHC), immunological indices (lysozyme activity, WBC, respiratory burst activity and phagocytic activity), improved apparent digestibility of nutrients (crude protein, crude fat, carbohydrates) and digestible energy. Furthermore, higher activity (P<0.05) of the digestive enzymes (cellulase, lipase and protease) and up-regulation of MyoD gene in muscle and TNF-α gene in liver, intestine, and muscle was also observed, while the activity of serum AST(serum aspartate aminotransferase) and ALT (Alanine transaminase) as compared to control group was significantly decreased (P<0.05) . Based on results, β-mannanase supplementation (500U/kg) could be recommended for obtaining better carp production when low-cost plant-protein rich diets are used.